Abandoned housing projects in Peninsular Malaysia : legal and regulatory framework - Nuarrual Hilal Md. Dahlan (Ahmad Ibrahim, Kulliyyah of Laws, International Islamic University Malaysia, 2009)
Abandoned housing projects are pathetic phenomena occurring in the housing industry in Peninsular Malaysia. Even though, the housing industry has developed and permeated throughout the nation since Independence day, a negative phenomenon that keeps recurring is abandoned housing projects. Though land, planning, building and housing laws as ,vell as their regulations have been passed by Parliament with the purpose of control ling and regulating the housing development industry in Peninsular Malaysia, it is regretted that, this catastrophe--abandoned housing projects are still common and persisting until today. Thus, certain review and study is required to reevaluate and re-examine the existing legal provisions and remedies, in particular the Housing Development Act 1966 (Act 118) and its Regulations, the Street, Drainage and Building Act 1974 (Act 133), the Town and Country Planning Act 1976 (Act 172), the Uniform Building By-Laws 1984 (ON .5178/84 ), the National Land Code 1965 (Act No. 56 of 1965) and other relevant legislations in order to find and investigate clear and potential legal weaknesses which have caused and could cause the abandonment and its consequences. This research, will be based on qualitative case study and will use legal research methods. It intends to explore the facts and the legal phenomena in two (2) abandoned housing projects viz, at Phase II, Taman Harmoni, Lot 82, Mukim of Cheras, District of Hulu Langat, Selangor and Phase I A, Taman Lingkaran Nur, KM 21, Jalan Cheras-Kajang, P.T No. 6443, H.S.(D) No. 16848, Mukim of Cheras, District of Hulu Langat, Selangor. From the research, it is hoped that certain findings in regard to their legal causes, the legal problems plaguing the said projects and legal approaches toward their rehabilitations can be established for future guidelines and suggestions to overcome the same. These will hopefully, assist the authorities concerned to adopt legal policies and take certain legal measures to avoid similar problems from recurring in the future. In case rehabilitation for abandoned housing projects are to be carried out, the findings and suggestions in this research can be applied for facilitating the rehabilitation until full completion.